Geant4 quartz fiber simulations as part of luminometer development for CMS. (December 2020) - Selivanova, D A; Popova, E V; Ilyin, A L; Aydilek, O; Ozkorucuklu, S; Cerci, S; Sunar Cerci, D
Abstract: Measurements of luminosity are required to be exceedingly accurate for the new upcoming era of the LHC with higher energies and a more complex structure of the beam (HL-LHC). A new device is being developed for the CMS experiment to fulfill demands of being stand-alone and precise. The paper describes the design, main components and physics behind the new quartz fiber based luminometer (QFL). Via simulations of a single quartz fiber, we were able to calculate an average number of photons reaching the end of the fiber after a single particle hit.